I Can Survive: The Dynamics of Sadness in Early Adulthood Who Experience the Death of a Parent Due to Illness - Fira, Syafira; Any Nurhayaty; Setriani (Psikoislamedia: Jurnal Psikologi, 2025)
The death of a parent is a difficult thing for a child even the child become adult grown up. Even child become adults, in reality they still need parental. The sadness because of parent due to illness has different grief than sudden death. This study describes the dynamics of individuals with the experience of parental death due to illness. Using qualitative design of two subjects. Data collection using Ross's & Kessler theory (2014). The research data were analyzed through data reduction, data display creation, and data interpretation. The results explain that two subjects did not go through the anger stage. The death of a parent with the same gender as the subject causes a change in the role played by the subject. Moreover, when the subject becomes the only man or woman in the family after the death of a parent. Male subjects' acceptance of parental death was achieved but not with willingness.  Keywords: Death of Parents, Sadness, Child, Early Adulthood, Illness